Acoustic factors in musical phonation : a study in off-pitch phenomenon - Jai Prakash Gupta (Journal of All India Institute of Speech and Hearing, 1970)
The present study was undertaken to study vocai behaviour of singers. It is generally assumed. that singers while singing a note are in perfect match with the theoretically calculated note. These relations between reference note and other notes are standard like between reference note and octave note ratio is 1 : 2. Studies on vocal abuse in singers shown above may not be true. Thus study of off-pitch behaviour was undertaken. This was studied in octave notes and extreme notes beyond octave.Related behaviour, viz., intensity frequency relation, maximum phonation duration, maximum pause duration, effect of sex On off-pitch was undertaken.